The impact of open distance learning (ODL) on students' performance in Universiti Teknologi MARA Kelantan branch / Azzieatul Syazwanie Azmi and Lai See May - Azmi, Azzieatul Syazwanie; See May, Lai (2021)
The Coronavirus (COVID-19) outbreak has impacted education systems globally, contributing to the near-total closing of schools, universities and colleges. The pandemic has pushed schools and higher education institutions to shift the teaching and learning classes from physical classrooms to various online platforms which help to minimise the spread of infections and ensure effective learning continues. Hence, Universiti Teknologi MARA (UiTM) has decided to implement Open Distance Learning (ODL) due to the massive attack of COVID-19 in Malaysia. The purpose of this study is to identify the impact of ODL on students' performance among students of UiTM Kelantan branch. Besides, this study seeks to examine the challenges faced by students in ODL classes. The empirical data of 70 students who participated through online survey were analysed using descriptive analysis. The findings of the study revealed that majority of the respondents are dissatisfied with their ODL experiences. Results also showed that students have lack of motivation and they are unable to adapt to this new learning environment. It can be concluded that majority of the students still need more time to adapt and adopt to the new norm of online learning environment. Even though ODL is recommended due to its flexibility, accessibility, affordability and life-based education opportunities, it is recommended that the university should equip students with independent study skills and recruit competent, creative and committed academics to enhance the teaching and learning of ODL in UiTM Kelantan branch